Pelatihan Implementasi Strategi Pembelajaran Bahasa dalam Pembelajaran Bahasa Dayak Ngaju di Sekolah Dasar - Iwan Fauzi; Dina Mardiana; Akhmad Syifa Ramadhani; Ririn Mahdiyani Safutri (J-ABDIPAMAS (Jurnal Pengabdian Kepada Masyarakat), 2022)
ABSTRACTThe Lecturer Program for Assisting Excellent Human Resources (PDPSU) is one of the schemes in the community service activities at the university which was carried out by the FKIP Lecturer Team from the University of Palangka Raya (UPR). The PDPSU program was implemented to six teachers of Dayak Ngaju Language (BDN) Subject at SD Muhammadiyah Pahandut and SDN-5 Panarung Palangkaraya city through training and assistance in implementing the strategy of language learning. The purpose of this PDPSU activity was to help fulfill the pedagogic competence of the BDN subject teachers in applying the theory of language learning strategy including techniques for using BDN learner dictionary and developing teaching materials, grammar translation teaching method, communicative approach, and language learning techniques in learning BDN at the elementary schools. The results of the program can improve teachers’ competence in mastering the basic concepts and theories of language learning strategy and apply them to develop the learners’ worksheet of BDN in the elementary schools and implementing them in learning activities within their respective classes. It showed by the observation grade attained by the teachers during training and mentoring reached an average of 81.6. Keywords: language learning strategy, Dayak Ngaju language, primary school ABSTRAKProgram Dosen Pendamping SDM Unggul (PDPSU) merupakan salah satu skim dalam kegiatan pengabdian kepada masyarakat di perguruan tinggi, yang dilaksanakan oleh Tim Dosen FKIP dari Universitas Palangka Raya (UPR). Program PDPSU ini dilaksanakan kepada enam orang Guru Mata Pelajaran Bahasa Dayak Ngaju (Guru Mapel BDN) di SD Muhammadiyah Pahandut dan SDN-5 Panarung Kota Palangkaraya melalui pelatihan dan pendampingan implementasi strategi pembelajaran bahasa. Tujuan kegiatan PDPSU ini untuk membantu memenuhi kompetensi pedagogik para guru mapel BDN tersebut dalam mengaplikasikan teori strategi pembelajaran bahasa yang mencakup teknik penggunaan kamus pelajar BDN dan pengembagan materi ajar, metode pengajaran terjemahan tata bahasa, pendekatan komunikatif, dan teknik pembelajaran bahasa dalam pembelajaran BDN pada sekolah dasar. Hasil kegiatan pada program PDPSU ini dapat meningkatkan kompetensi guru dalam menguasai konsep dasar dan teori strategi pembelajaran bahasa dan mengaplikasikannya dalam bentuk pengembangan LKPD pembelajaran BDN di sekolah dasar serta mengimplementasikannya pada kegiatan pembelajaran BDN di kelasnya masing-masing. Hal itu ditunjukkan dengan nilai pengamatan terhadap aktivitas dan kinerja guru saat pelatihan dan pendampingan, yakni rata-rata 81,6.  Kata kunci: strategi pembelajaran bahasa, bahasa Dayak Ngaju, sekolah dasar